PACKAGING AND MARKETING OPTIMIZATION FOR RURAL COMMUNITY ENTERPRISES: ENHANCING PRODUCT VALUE AND ADVANCING THE SDGS - Adawiyah, Robiatul; Murtikusuma, Randi Pratama; Triana, Renka Mey (LP2M Universitas Ibrahimy, 2025)
Packaging design and marketing strategy play an important role in improving product competitiveness, especially for community-based enterprises in rural areas that focus on local economic development. Tanggul Wetan Village offers a variety of superior products made by local business communities, such as bolen, getuk singkong, and prol tape, which have great potential to expand into wider markets. However, several challenges remain, including the lack of innovation in packaging design, the limited use of digital marketing technology, and the absence of effective and sustainable promotional strategies. This community service activity aimed to analyze and develop optimal strategies in packaging design and marketing to enhance product excellence and support the achievement of the Sustainable Development Goals (SDGs), particularly SDG 8, SDG 10, and SDG 12. The program was implemented using the ADDIE training model, which consists of five stages: analysis of community needs, design of training approaches, development of training materials, implementation of training, mentoring and assistance, and finally, evaluation. The results showed a significant improvement in participants’ abilities to create attractive and informative packaging, as well as an increased understanding of digital marketing platforms. Based on pre- and post-assessment data, participants demonstrated measurable progress: packaging design skills increased from 2.3 to 4.1, branding and logo from 1.9 to 3.8, marketing strategy from 2.5 to 4.3, digital marketing from 1.7 to 3.9, and content creation from 2.0 to 4.0 (on a 1–5 scale). Several products were successfully rebranded with better packaging and labeling, making them more competitive in the market. This activity not only increased the marketability of local products but also demonstrated the importance of design and marketing innovation as a pathway for empowering rural communities and supporting inclusive and sustainable economic growth.